(untitled) (Research, Society and Development, 2021)
The aims at identifying and describing the occurrence ofanatomopathological and histopathological changes in Nile tilapia juveniles, naturally infected with Francisella noatunensis subsp. orientalis (Fno). The Nile tilapias of this study were cultivated in net cages in the region of the Araguari River basin, Minas Gerais, Brazil, and due to a mortality rate ranging from 40 to 60%, 64 fish samples were collected and sent for examination in the laboratory. At necropsy, granuloma-like nodules were observed in the spleen 59/64(92.2%), kidney 24/64 (37.5%), and liver 09/64 (14.1%). Fno was detected in 98% (49/50) of the samples by PCR. Upon analysis, astrong correlation was observed between external and internal lesions, since granulomatous lesions present in the spleen and kidney of the same animal simultaneously were also accompanied by skin ulcers, suggesting that the cutaneous lesion is related to the presence of Fno in tilapia and can be used as an indication for early diagnosis. Thus, the high prevalence of Fno observed in this research study allows characterizing an outbreak in the region. It is noteworthy that especially regarding the consumption of tilapia meat, although there are zoonotic species in the Francisella group, the zoonotic potential of Fno is not yet known and should be further studied.